A segunda navegação de Sócrates e dialética - Delcomminette, Sylvain (Revista Archai, 2015)
Abstract: In this paper, I examine the famous passage of the Phaedo where Socrates explains the methodology of his ‘second sailing’ (99d-102a) and I try to relate this methodology to dialectic as it is presented in other dialogues. I suggest that the method Socrates describes has two steps. The first step, which is the only one practised in the Phaedo, consists not merely in positing hypotheses, but in positing the safest possible hypothesis, i.e. the hypothesis of Forms, and in building explanations consistent with it. The second step, which is only announced in the Phaedo without being put to use, corresponds to what Plato calls ‘dialectic’ in the Republic, which itself corresponds to the method of collection and division practised in later dialogues, and has the aim, not to prove the hypotheses posited in the first step, but to clarify or define them. Thus understood, this passage makes it possible to see a profound unity in Plato’s methodology. Keywords: Dialectic, Hypothesis, Methodology, Division, Definition.